Scottish Ambulance Unit : memorandum of telephone conversation - Stevenson, Daniel M., Sir ; McDonald, Florence
041-0053-001 MEMORANDUM OF INTERVIEW. Date 23rd March, 1937. Reference FEM/MT/678 Time to Present Sir Daniel Stevenson and Miss Mc.Donald. SUBJECT. Scottish Ambulance Unit. Telephone Conversation. Sir Daniel Stevenson telephoned this afternoon while Sir Walter was engaged. He wanted to come along and see him and shake hands with him and thank him for what the Council has done for the Scottish Ambulance Unit. In view of information he had had, he sent a wire last night to the Unit telling them to leave Madrid and go eastward. He did this because he was given to believe there is the danger of Madrid being surrounded and starved. A Unit would be no good in a starving city and there are some places Eastward where their help is very badly needed. He would be glad of any suggestions from Sir Walter. 292/946/41/53